2021
DOI: 10.3390/ma14216389
|View full text |Cite
|
Sign up to set email alerts
|

Declining Performance of Silicone-Based Magnetorheological Elastomers after Accelerated Weathering

Abstract: Magnetorheological elastomers (MRE)-based products are usually located in an area directly exposed to sunlight and rain. However, there is no specific research on the behavior of MRE after accelerated weathering. Therefore, in this study, the changes to the chemical and rheological properties of both isotropic and anisotropic MRE after accelerated weathering were examined. Treated and untreated specimens were compared. MRE specimens with 40% by weight CIP were prepared with no current excitation and another sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Natural weathering in a tropical climate exhibited a distinct degradation process, with dry and wet conditions averaging 27.5 °C and 287.5 mm rainfall with 74.3% humidity, respectively. Previous research [ 17 ] on accelerated weathering of MRE found that the G’ decreased by up to 85% with increasing magnetic strength after the accelerated weathering condition. These findings, however, were established under much more aggressive conditions, such as a difference of 120% in temperature and at least a 20% difference in humidity in comparison to the current study.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Natural weathering in a tropical climate exhibited a distinct degradation process, with dry and wet conditions averaging 27.5 °C and 287.5 mm rainfall with 74.3% humidity, respectively. Previous research [ 17 ] on accelerated weathering of MRE found that the G’ decreased by up to 85% with increasing magnetic strength after the accelerated weathering condition. These findings, however, were established under much more aggressive conditions, such as a difference of 120% in temperature and at least a 20% difference in humidity in comparison to the current study.…”
Section: Resultsmentioning
confidence: 98%
“…The outdoors [ 15 ] is one of the most demanding service environments, with weather conditions having a strong correlation. Weathering [ 16 , 17 , 18 , 19 ] accelerates the undesirable change caused by outdoor exposure, and the climate atmosphere influences the weathering condition over relatively long periods. As the MRE industry has evolved, significant effort has been expended to understand the degradation of MRE during weathering in various climates, with the focus on tropical climates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation